Perancangan Antarmuka Pengguna Sistem Informasi Penilaian Kinerja Guru Menggunakan Human Centered Design (HCD) (Studi Kasus: SMP Islam Sabilurrosyad Malang) - Mardiana Dwi Muliani; Ismiarta Aknuranda; Alfi Nur Rusydi (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
The teacher is a professional educator who has a big task and responsibility to educate the nation's generation. Schools must improve teacher professionalism by evaluating teacher performance. SMP Islam Sabilurrosyad is a secondary level education under the shade of the Islamic Education Foundation of Malang City. It has not implemented teacher performance assessment. SMP Islam Sabilurrosyad didn't yet have the mechanism and rules of PKG. So that, made the gap between teachers because it could have an impact on the unfairness of schools in giving the rights of teachers or educators by the competencies, assessment indicators, and other supporting activities. Based on the problems that occur, the researcher designed the web-based information system user interface to help the teacher performance evaluation process. The approach taken uses Human-Centered Design (HCD) to fulfill user needs and facilitate users using the system so could be given satisfaction to users. The design was produced in this study were two high fidelity prototype designs, then evaluated using the usability testing technique with the Single Ease Question (SEQ) method to four respondents as users. Testing was done to measure the level of user convenience in working on the task scenario. The test results are based on data obtained that the tasks given can be done easily by respondents but need improvement based on suggestions given by respondents.